Physical exercise as a non-pharmacological therapeutic strategy in hospital care: a systematic review (Research, Society and Development, 2022)
Aging is a human condition understood as a sequential, individual, cumulative, irreversible, universal, non-pathogenic and organism-modifying process. In this process, there may be injuries that induce progressive molecular and cellular damage, so that over time the organism becomes less capable of dealing with the stress of the environment; contributing to the onset of illness and hospitalization. An important consequence of prolonged hospital bed rest in the elderly is the significant loss of muscle mass and strength underlying the accelerated deficits in physical performance. The aim of this study was to review the scientific literature on the effectiveness of physical exercise as a non-pharmacological intervention strategy in hospital care. Searches were carried out in the following databases used in health research: PUBMED, LILACS, ScienceDirect, SCOPUS, SCIELO and CAPES. The articles selected for the research should involve research on the intervention with physical exercises in hospital care for elderly patients. The analysis method followed PRISMA guidelines. After applying the inclusion and exclusion criteria and detailed analysis of the articles, the final sample consisted of 12 articles. The present systematic literature review reveals that all identified articles have a quantitative approach. In general, the articles reveal benefits for the intervention with physical exercises in hospital care with improvements in the following aspects: physical fitness, submaximal aerobic capacity, functional mobility, time to hospital discharge, muscle strength and cognitive function, movement pattern, cardiac rehabilitation, gait speed and pain.